The canonical connection between motor abilities and situationalmotor elements of the water polo game - Dizdar, A.; Mirvic, E.; Lemeš, D.; Bazdarevic - Rašidagic, A. (Sportski Logos, 2020)
The main goal of this research is to determine the relations and the influence of motor abilities on the result in performing situational - motor elements of the water polo game in water polo players aged 13 to 15 years old. The variables measured in this sample are as follows: In the motor skills field, 12 tests were applied that represent the basis of motor skills in the water polo game. In the field of situational - motor tests, 6 tests were applied, which represent the basis for the application of elements of water polo technique in the situational conditions of the game. For a better quality analysis of the treated variables, as well as the magnitude of the mutual influences, canonical correlation analysis was applied. Based on the obtained results of the canonical correlation analysis of motor abilities and situational - motor elements of the water polo game, significant connections between the treated areas were obtained. It can be concluded that water polo players, who have a higher (general) level of all applied basic motor skills, especially explosive and static strength, agility, speed endurance in swimming with water polo crawl, flexibility of the whole body have a greater opportunity to achieve better results in situational - motor elements of the water polo game which makes one team more successful.